Proceedings from the Gatorade International Triathlon Science II Conference, Noosa, Australia, November 7-8, 1999 (1999)
Collection of the proceedings held at the Gatorade International Triathlon Science II Conference, Noosa, Australia, November 7-8, 1999. Content: Ron Clarke - Maximising Athletic Performance Dr John Hellemans - Maximising Olympic Distance Triathlon Performance - A Sports Medicine Perspective Dr Darren Smith - -Maximising Olympic Distance Triathlon Performance: A Sports Physiologist's perspective Ian Hellemans - Maximising Olympic Distance Triathlon Performance: A Sports Dietitians Perspective Brian McLean - Maximising Olympic Distance Performance - A Biomechanist's Perspective Chris Hill - Maximising Olympic Distance Performance - The Athlete`s Perspective Kieran Barry - Maximising Olympic Distance Triathlon Performance: A Coach's Perspective Rod Cedaro Using hypobaric oxygen techniques and hyperbaric intervention to level the playing field in olympic distance triathlon Sally A Clark, Julie Dixon, Christopher J Gore, and Allan G Hahn - 14 Days of Intermittent Hypoxia Does Not Alter Haematological Parameters Amongst Endurance Trained Athletes John Hellemans - Intermittent Hypoxic Training: A pilot Study Dave Bishop - Reliability and validity of portable lactate analysers? Grant Landers - Kinanthropometric differences between World Championship senior and junior elite triathletes B. Davoren and J. Gregory - The effects of three varied cycle leg protocols on self-paced run time trial performance. John Hellemans - Lactate Index and training load Ian Hellemans - Fluid losses and Voluntary Fluid Intakes in New Zealand Age Group Triathletes During the 1998 ITU World Championship Triathlon Aaron Coutts, Peter Reaburn, Kerry Mummery, and Grant Schofield - Sweat loss, Fluid intake and triathlon performance in hot and humid conditions. Asker Jeukendrup - Fat loading and Carbohydrate Loading in Endurance Athletes.